Dynamic Loading Effect on Fault Current and Arc Flash for a Coordinated Substation - A. B. M. Shafiul Azam (IEEE Access, 2021)
Due to load growth and various load types within the service territory, utilities need to enhance the utilization of substations. In any case, towards the coordinated substation design, the utilization of the transformers’ most total capacity cannot be reduced just because there is a lack of proper coordination between transmission and distribution systems. The transmission and distribution systems’ stability and safe operability must be investigated in a coordinated substation. The critical issues are the asymmetric fault currents on the high voltage and arc-related safety issues on the distribution switchgear at different dynamic loading scenarios. We found that when one 138 kV transmission line and two transformers are energized, with increased dynamic loading, from 40% and above, the substation, as a whole, gets gradually more stressed. Because of the highest amount of fault currents on the 138 kV bus, to avoid CT saturation, we need to consider that three transmission lines are connected, and all three transformers are running at 100% dynamic loading. At this value of dynamic loading, in the 13.2 kV switchgear, the incident energy is 2 cal/cm2, and the arc flash boundary is four feet, which ensures that all workers need to wear the proper arc-rated clothes to work on any de-energized cubicle of the switchgear.